Strategi Akselerasi Insurtech Syariah Meningkatkan Nasabah Pengguna Asuransi di Indonesa (Studi Kasus Startup YukTakaful ) - -, Lindiawatie; Shahreza, Dhona (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2021)
In 2019, the sharia insurance market share in Indonesia was only 3.44%. The reason is the low level of literacy and inclusion of sharia insurance. On the other hand, there are opportunities and potentials that allow the growth and increase of sharia insurance market share in Indonesia. For this reason, an acceleration strategy is needed to increase the market share of sharia insurance in Indonesia through insurance technology. The purpose of this study is to determine the acceleration strategy in reaching the insurance market in Indonesia by highlighting the case of the YukTakaful InsurTech startup. This type of research is qualitative based on phenomenology. Methods of collecting data by semi-structured interviews with the founder and management as well as documentation. Analysis and interpretation of data with a literature study approach. After the analysis, it is known that the acceleration strategy to increase the market share of sharia insurance in Indonesia with a case study on the YukTakaful startup is to go through the stages starting from setting focused and clear goals, creating a vision and mission that brings benefits and has social impact (maslahah). focusing on community and community-based segmentation and targets, building a network of cooperation in the business ecosystem (alliance strategy) and communicating and educating consumers through offline and online communication channels as well as collaboration with the fintech ecosystem and community customers (market penetration strategy). Alliance strategy by establishing cooperation with venture capital, server providers, data centers, data recovery centers and cloud computing insurance brokers and insurance companies. Market penetration strategy by targeting the community segment, focusing on basic protection with types of micro insurance products, end to end process services in real time 2x24 hours, maintaining the trust and comfort of consumers by maintaining the security and confidentiality of their data. Â